Toba Batak Cultural Values as a Foundation for Advancing Tourism in the Global Samosir Regency - Harisan Boni Firmando (Malikussaleh Social and Political Reviews, 2023)
The current phenomenon is that many Toba Batak people do not understand cultural values so that cultural values as a foundation for advancing tourism are not used properly. The purpose of this study is to find out how the cultural values of the Toba Batak are the foundation for advancing tourism, which includes the work ethic of the Toba Batak people and the actualization of cultural values to advance tourism in the worldwide Samosir Regency. This study uses qualitative methods to understand social phenomena. The results of the study show that cultural values which cover all aspects of the life of the Toba Batak people are grouped into nine values. The cultural values of the Toba Batak people are actualized in various philosophical expressions that guide behavior, including how to interact socially. This philosophical expression is a motivation for the Batak Toba community so that it becomes a work ethic to be able to achieve and achieve goals. In order for cultural values to be actualized to advance tourism, it is necessary to organize by the social system in society. The role of regional leaders, such as raja huta (village), natua-tua ni huta (parents/elders of the village) and modern village institutions led by hamung (village heads) is urgently needed to educate local wisdom values to the community and organize various activities that can foster solidarity. The concrete form of solidarity is through cooperation that has long existed in society. In order for collaboration in the community to be sustainable, assistance is needed by various parties, both the government, the private sector, and the Toba Batak community from Samosir Regency.